2015
DOI: 10.3329/jemc.v5i1.21495
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Azithromycin in Typhoid and Paratyphoid Fever in Children

Abstract: Background: Azithromycin sensitivity cannot precisely identify the strains of typhoid and paratyphoid fever for successful treatment. Most of the studies show that azithromycin is highly effective in uncomplicated typhoid fever. Very few studies have been carried out in Bangladesh to see the effectiveness and sensitivity of azithromycin in children with uncomplicated typhoid fever. Objective: To assess the clinical response of azithromycin in uncomplicated typhoid fever. Materials and Methods: This randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…This comparative study between azithromycin and ciprofloxacin for uncomplicated enteric fever in children displayed high responsiveness of azithromycin with clinical efficacy more than 90%, resembling the results of many studies done previously. 8,18,19 Few studies reported the efficacy of azithromycin therapy in adults but not significant enough in children, contrary to our results where majority responded well to azithromycin. 20,21 The optimal dosing regimen of azithromycin for the treatment of enteric fever is yet to be determined.…”
Section: Discussioncontrasting
confidence: 94%
“…This comparative study between azithromycin and ciprofloxacin for uncomplicated enteric fever in children displayed high responsiveness of azithromycin with clinical efficacy more than 90%, resembling the results of many studies done previously. 8,18,19 Few studies reported the efficacy of azithromycin therapy in adults but not significant enough in children, contrary to our results where majority responded well to azithromycin. 20,21 The optimal dosing regimen of azithromycin for the treatment of enteric fever is yet to be determined.…”
Section: Discussioncontrasting
confidence: 94%
“…A total of 97.6% of those who were sensitive to azithromycin improved, whereas only 78% of those who were resistant did so. The majority of patients who had developed resistance to azithromycin exhibited clinical improvement after therapy with this medicine, according to a study that were similar to ours and found the same thing in the azithromycin group (10).…”
Section: Discussionsupporting
confidence: 82%
“…Six studies met the criteria for inclusion and subsequent data extraction. The six studies ( 13,14,15,16,17,18 ) included 520 patients. The risk of bias assessment of all six trials was generally low risk (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…This study aimed to investigate the efficacy of oral azithromycin against parenteral ceftriaxone in the treatment of uncomplicated typhoid fever, and whether intravenous drugs may be replaced with oral azithromycin for the convenience and for better compliance among pediatric patients [12][13][14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%